Hopping rim to rim through the Golgi - Pfeffer, Suzanne R (eLife Sciences Publications, Ltd, 2013)
A novel approach based on tracking the fate of proteins that become ‘stapled’ to the walls of the Golgi yields insights into the long-sought mechanism of transport through this organelle.